In‐house high‐energy‐remote SAD phasing using the magic triangle: how to tackle the P1 low symmetry using multiple orientations of the same crystal of human IBA57 to increase the multiplicity. Issue 3 (5th April 2019) - Gourdoupis, Spyridon; Nasta, Veronica; Ciofi-Baffoni, Simone; Banci, Lucia; Calderone, Vito
Abstract : This article describes the methodological approach used to solve the structure of human IBA57; to our knowledge, this is the only structure present in the Protein Data Bank which has been solved in‐house by remote SAD phasing in space group P 1 using only one crystal. Abstract : This article describes the approach used to solve the structure of human IBA57 in‐house by 5‐amino‐2, 4, 6‐triiodoisophthalic acid (I3C) high‐energy‐remote single‐wavelength anomalous dispersion (SAD) phasing. Multiple orientations of the same triclinic crystal were exploited to acquire sufficient real data multiplicity for phasing. How the collection of an in‐house native data set and its joint use with the I3C derivative through a SIRAS approach decreases the data multiplicity needed by almost 50% is described. Furthermore, it is illustrated that there is a clear data‐multiplicity threshold value for success and failure in phasing, and how adding further data does not significantly affect substructure solution and model building. To our knowledge, this is the only structure present in the PDB that has been solved in‐house by remote SAD phasing in space group P 1 using only one crystal. All of the raw data used, derived from the different orientations, have been uploaded to Zenodo in order to enable software developers to improve methods for data processing and structure solution, and for educational purposes.